Frequency of Aspirin Resistance in Ischemic Stroke Patients and Healthy Controls from Colombia (2021)
ABSTRACT: Objective: To evaluate the aspirin resistance prevalence in patients with previous ischemic cerebrovascular disease undergoing aspirin therapy for secondary prevention. Materials and methods: Three hundred fifty patients presenting ischemic strokes and 100 healthy controls under aspirin treatment were evaluated using the optic platelet aggregation test. Results: Aspirin resistance was found in 7.4% of the patients with ischemic stroke and 4% of controls. Aspirin resistance was associated with stroke recurrence in univariate analysis (p = 0.004). Aspirin resistance was not associated with smoking, diabetes, or hypercholesterolemia. Conclusion: Aspirin resistance is present in Colombian patients with ischemic stroke as well as in healthy controls.